Complicity in international law - Jackson, M (2013)
This thesis is concerned with the ways in which international law regulates state and individual complicity. Complicity is a derivative form of responsibility that links an accomplice to wrongdoing by a principal actor. Whenever complicity is prohibited, certain questions arise about the scope and structure of the complicity rule. To answer these questions, this thesis proposes an analytical framework in which complicity rules may be assessed, and defends a normative claim as to their optimal structure. This framework and normative claim anchor the thesis’ analysis of complicity in international law. The thesis shows that international criminal law regulates individual complicity in a comprehensive way, using the doctrines of instigation and aiding and abetting to inculpate complicit participants in international crimes. These doctrines are marked by the breadth of the complicit conduct prohibited, a standard of knowledge in the fault required of the accomplice, and an underused nexus requirement between the accomplice’s acts and the principal’s wrong. In contrast, international law’s regulation of state complicity was historically marked by an absence of complicity rules. In respect of state complicity in the wrongdoing of another state, international law now imposes both specific and general complicity obligations, the latter prohibiting states from aiding or assisting another state in the commission of any internationally wrongful act. In respect of the ways that states participate in harms caused by non-state actors, the traditional normative structure of international law, which imposed obligations only on states, foreclosed the possibility of regulating the state’s participation as a form of complicity. As that traditional normative structure has evolved, so the possibility of holding states responsible for complicity in the wrongdoing of non-state actors has emerged. More and more, both the wrongs that international actors commit, and the wrongs they help or encourage others to commit, matter.